IMPROVING STUDENTS’ ACHIEVEMENT IN NARRATIVE WRITING THROUGH CONSULTANCY PREWRITING PROTOCOL - Rafita Tioria Sianipar (Jurnal Christian Humaniora, 2019)
Abstract: This study attempted to improve students’ achievement in narrative writing by applying Consultancy Prewriting Protocol Technique. This study was conducted by using classroom action research. The subject of this research was the students of second year of one of senior high schools in Medan with the total of 43 students. The research was conducted into two cycles consisted of six meetings. The instruments for collecting the data were tests, diary notes, observation sheets, and interview. Based on the data analysis, the mean of the students’ score for the orientation test was 52.51, for test I (cycle 1) was 61.39 and for test II (cycle 2) was 76.58. The conclusion is Consultancy Prewriting Protocol Technique can improve the students’ achievement in narrative writing.Keywords: Students achievement, narrative writing, Consultancy Prewriting Protocol